Sunrise [videorecording (DVD)] - Hussain, Adil; Chatterjee, Tannishtha; Ansari, Gulnaaz ([Publisher not identified], 2016)
A Social Services officer Lakshman Joshi, whose bad past and current reality begin to converge as he investigates a kidnapping ring within the rain-soaked back alleys and seedy nightclubs of urban Mumbai.